A nanoliposome encapsulating tuna uricosuric acid-lowering peptide

By encapsulating the tuna uric acid-lowering peptide in nanoliposomes and homogenized by using dynamic high-pressure microjet technology, the problem of easy degradation of bioactive peptides in the gastrointestinal environment is solved, and the stability and bioavailability of the peptide are improved.

CN118480085BActive Publication Date: 2025-03-14OCEAN UNIV OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410554742.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-07
Publication Date
2025-03-14
Estimated Expiration
2044-05-07

AI Technical Summary

Technical Problem

Bioactive peptides are easily degraded in the gastrointestinal environment, resulting in limited use of their foods, and it is difficult for short peptides to maintain integrity during in vivo delivery.

Method used

Nanoliposomes are used to encapsulate tuna peptides with uric acid-lowering activity, and a phospholipid bilayer structure composed of soy lecithin and cholesterol is formed to form nano-scale liposomes with particle size less than 120nm, and homogenized by dynamic high-pressure microjet technology.

Benefits of technology

Effectively protect peptides from gastrointestinal digestion, improve their stability and bioavailability, ensure full absorption in the small intestine, and have good sustained release characteristics and storage stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118480085B_ABST
    Figure CN118480085B_ABST
Patent Text Reader

Abstract

The present invention provides a nanoliposome encapsulating tuna uric acid-lowering peptide, comprising a core material and a wall material, wherein the core material comprises the above-mentioned polypeptide having uric acid-lowering activity, the amino acid sequence of the polypeptide being SEQ ID NO: 1; and the wall material comprises soybean lecithin and cholesterol. The present invention adopts dynamic high-pressure microfluidization technology to encapsulate the uric acid-lowering peptide, and prepares nano-scale liposomes with small particle size and good stability, which have good sustained-release properties, and not only solve the problem that the structure of the uric acid-lowering peptide is easily destroyed in the gastrointestinal environment, but also its nano-scale size gives it special intestinal cell absorption ability. The activity of the nanoliposome encapsulating the uric acid-lowering peptide is mostly retained after being digested by simulated gastrointestinal fluid, and it has good storage stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of active biological products, and particularly relates to a nanoliposome encapsulating tuna uricosuric acid-lowering peptide. Background Art

[0002] The utilization of the potential biological effects of peptides depends mainly on their ability to maintain activity and integrity until reaching the target delivery site. However, the sensitivity of these bioactive peptides to the acidic conditions in the stomach and different enzymes in the gastrointestinal tract limits their application in food. It is reported that orally ingested bioactive peptides encounter the action of at least 40 different enzymes before entering the systemic circulation, so the applicability of bioactive peptides may be limited by their low stability, resulting in degradation and loss of activity. Encapsulation of peptides into carrier systems can not only mask their bitter taste but also improve stability and bioavailability. Nanoliposomes have been applied to encapsulate various hydrophilic, hydrophobic and amphiphilic bioactive compounds, such as essential oils, vitamins, polyphenols, fatty acids, phytosterols, proteins, peptides, enzymes and anthocyanins.

[0003] The research on the physiological activity of short peptides has been carried out extensively at home and abroad, but the research on its practical application is obviously insufficient. After passing through the gastrointestinal digestive enzyme system and the highly acidic environment, short peptides are severely degraded. After entering the small intestinal cells, they will be degraded by peptidases. Therefore, the possibility that short peptides can exert physiological activity in a complete state is very small, which makes most research unable to carry out practical applications. Therefore, analyzing the protein modification mechanism and the complete transport process of short peptides provides a theoretical reference for the in vivo delivery of short peptides, which is of great significance for the high-value utilization of proteins and the development of the short peptide nutrition industry.

[0004] Liposomes, also known as lipid globules, are closed vesicles that embed drugs in a phospholipid bilayer structure formed by amphiphilic lipid molecules. Similar to the cell membrane structure, they are mainly composed of phospholipids and cholesterol. Liposomes can embed both water-soluble and fat-soluble drugs. As drug carriers, liposomes are highly valued and widely used because of their easy degradation in the body, non-immunogenicity, non-toxicity, ability to control drug release, and reduced toxicity. Summary of the invention

[0005] The object of the present invention is to provide a nanoliposome encapsulating a tuna uric acid-lowering peptide, so that the polypeptide with uric acid-lowering activity will not be affected by gastrointestinal digestion and can be fully absorbed in the small intestine.

[0006] The present invention first provides a polypeptide with uric acid-lowering activity, wherein the amino acid sequence of the polypeptide is DGFDGL (SEQ ID NO: 1).

[0007] The polypeptide provided by the present invention can be used to prepare a product for lowering uric acid. In an embodiment of the present invention, the product is a nanoliposome;

[0008] In another aspect, the present invention provides a nanoliposome, comprising a core material and a wall material, wherein the core material contains the above-mentioned polypeptide having uric acid-lowering activity.

[0009] The wall material comprises soybean lecithin and cholesterol, wherein the mass ratio of soybean lecithin to cholesterol is 1:6-14;

[0010] Furthermore, the mass ratio of the soybean lecithin to cholesterol is 1:12.

[0011] The nanoliposome provided by the present invention is prepared by mixing a core material solution and a wall material solution evenly, performing ultrasonic treatment, and then performing dynamic high-pressure microfluidization homogenization treatment to obtain nanoliposomes encapsulating uricosuric peptide with a particle size of less than 120nm and a potential of less than -20mV.

[0012] The volume ratio of the core material solution to the wall material solution is 2 to 14:1, preferably 11:1;

[0013] The preparation method, wherein the homogenization pressure is 50MPa.

[0014] The present invention uses dynamic high-pressure microfluidization technology to encapsulate uric acid-lowering peptides and prepare nano-sized liposomes with small particle size and good stability, which have good sustained-release properties. It not only solves the problem that the structure of uric acid-lowering peptides is easily destroyed in the gastrointestinal environment, but also its nano-sized size gives it special intestinal cell absorption ability. The activity of the nano-liposomes encapsulating uric acid-lowering peptides is mostly retained after being digested by simulated gastrointestinal fluid, and it has good storage stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is the secondary mass spectrum of hexapeptide DL6.

[0016] Figure 2 The IC50 value data of the hexapeptide DL6 XOD inhibitory activity is shown in Figure 2.

[0017] Figure 3 This is the optimization diagram of TAP-NLs cholesterol-lipid ratio.

[0018] Figure 4 is the optimization diagram of the core-to-wall ratio of TAP-NLs,

[0019] Figure 5 is the optimization diagram of TAP-NLs homogenization pressure,

[0020] Figure 6 This is the optimization diagram of TAP-NLs ultrasound time.

[0021] Figure 7 Transmission electron microscopy images of TAP-NLs.

[0022] Figure 8 is the infrared spectrum of TAP-NLs,

[0023] Fig. 9 is the X-ray diffraction pattern of TAP-NLs,

[0024] Fig.10 The digestion stability of TAP-NLs.

[0025] Fig.11 This is the storage stability diagram of TAP-NLs. DETAILED DESCRIPTION

[0026] The present invention utilizes nanoliposomes to encapsulate uric acid-lowering peptides, which is beneficial to protect them from the influence of gastrointestinal digestion and limit the effect of the peptides to target cells, providing a theoretical basis for the application of uric acid-lowering peptides.

[0027] In the following examples, the method for measuring XO inhibitory activity by colorimetry is as follows:

[0028] (1) Solution preparation

[0029] 0.2 mol / L (pH 7.5) phosphate buffer (PBS): Accurately weigh 30.0838 g Na2HPO4·12H2O and 2.4962 g NaH2PO4·2H2O, dissolve them in deionized water, and make up to 500 mL.

[0030] Xanthine solution: Accurately weigh 6.4 mg of xanthine, dissolve it in 1 mL of 1 M NaOH, then add 100 ml of PBS and adjust the pH to 7.5 with 1 M HCl.

[0031] Xanthine oxidase: Take 120 μL of enzyme solution and dilute to 8 mL with PBS.

[0032] Allopurinol: Accurately weigh 1 mg of allopurinol and dilute to 100 mL to prepare 10 μg / mL allopurinol.

[0033] (2) Sample pretreatment:

[0034] Prepare samples at different concentrations, add 50 μL of the sample to be tested (or water as a control) and 50 μL of 0.02U / mL xanthine oxidase solution to each well of a 96-well plate, shake for 30 seconds, keep warm at 25°C for 5 minutes, add 150 μL of 0.48mM xanthine solution, shake for 30 seconds, keep warm at 25°C for 25 minutes, add 80 μL of 1M hydrochloric acid to measure the absorbance at 290nm. Each sample needs to be blanked, that is, add 80 μL of 1M hydrochloric acid at the same time as the enzyme is added.

[0035] (3) Calculation formula

[0036]

[0037] Where:

[0038] A1——absorbance of sample solution with enzyme added;

[0039] A2——Absorbance of sample solution without enzyme

[0040] A3——Absorbance of blank group with buffer replacing sample solution

[0041] A4——Absorbance of blank group without enzyme.

[0042] In the following examples, the particle size and Zeta potential of TAP-NLs were analyzed as follows:

[0043] The particle size and zeta potential of TAP-NLs were measured using a Zetasizer Nano potential and nanoparticle size distribution analyzer. Each sample was measured in triplicate.

[0044] In the following examples, the infrared determination method of TAP-NLs is as follows:

[0045] Fourier transform infrared spectroscopy (FTIR) analysis of liposomes was performed using a Fourier transform infrared spectrometer. The spray-dried TAP-NLs were mixed with potassium bromide (KBr) at a ratio of 1:100 and made into discs by a pressing device. The sample was analyzed using a Fourier transform infrared spectrometer (FTIR) with the following parameters: scanning range 4000-400cm -1 , the scanning number was 64 times, and the resolution was 1.0 cm-1. The FTIR data of TAP before and after embedding were analyzed using OMNIC 9.0 software.

[0046] In the following examples, the transmission electron microscopy analysis method of TAP-NLs is as follows:

[0047] The microstructure of the TAP-NLs suspension was observed using a transmission electron microscope (TEM). The TAP-NLs suspension was placed on a carbon-coated copper grid, and the excess sample was removed with filter paper. Subsequently, a phosphotungstic acid solution (1%, w / w) was added to the carbon grid, air-dried, and photographed.

[0048] In the following examples, the X-ray diffraction analysis method of TAP-NLs is as follows:

[0049] X-ray diffraction (XRD) analysis was performed using an accelerating voltage of 40 kV and an accelerating current of 40 mA. A certain amount of TAP-NLs and TAP were placed in the mold and scanned from 4° to 60° (2θ) at a speed of 6° / min.

[0050] In the following examples, the digestion stability analysis method of TAP-NLs is as follows:

[0051] Prepare simulated gastric fluid (SGF) and simulated intestinal fluid (SIF). Mix TAP with 1.25×SGF digestion solution (final concentration of pepsin is 2,000U / mL), add CaCl2(H2O)2, adjust pH to 3.0 with hydrochloric acid, and add water to 50mL. Finally, place the reaction system in a constant temperature oscillator and shake at 37°C. Samples are taken at 0, 60, and 120 minutes, named G0, G60, and G120, and placed at -20°C for subsequent index analysis.

[0052] The gastric digestion fluid was mixed with 1.25×SIF digestion fluid (pancreatic enzyme concentration was 1000U / mL, bile salt concentration was 100mM), and CaCl2(H2O)2 was added at the same time. The pH was adjusted to 7.0 with hydrochloric acid and water was added to make up to 50mL. Finally, the reaction system was placed in a constant temperature oscillator and shaken at 37°C. Samples were taken at 0, 60 and 120min, named I0, I60 and I120, and placed at -20°C for subsequent index analysis.

[0053] In the following examples, the storage stability analysis method of TAP-NLs is as follows:

[0054] The storage stability of TAP-NLs at different temperatures (-18°C, 4°C and 25°C) was studied, and the changes in particle size and zeta potential after storage for 0, 3, 7, 14, 21 and 28 days were investigated.

[0055] The present invention is described in detail below in conjunction with specific embodiments and drawings.

[0056] Example 1: Preparation of uricosuric acid-lowering peptides with XOD inhibitory activity

[0057] The polypeptide tuna peptide (TAP) with uric acid lowering peptide activity was obtained by enzymatic hydrolysis of yellowfin tuna minced meat. The specific enzymatic hydrolysis method was as follows: yellowfin tuna minced meat was homogenized, the homogenized fish paste was added with distilled water at a ratio of 1:4, and then 0.8% alkaline protease based on the weight of fish meat was added, the pH value of the system was adjusted to 8.5, and the mixture was hydrolyzed at 55°C for 4 hours to obtain the polypeptide TAP.

[0058] The amino acid sequence of TAP was identified by UHPLC-Q-Orbitrap, and the chromatographic column used was Agilent Advance-Bio Peptide Map C18 column (2.1×150 mm, 2.7 μm). UHPLC parameters: mobile phase A: 0.1% formic acid-acetonitrile, mobile phase B: 0.1% formic acid-water, flow rate: 0.25 mL / min, column temperature: 40°C, gradient elution program 0-2 min (5% A), 2-27 min (5% A-20% A), 27-37 min (20% A-35% A), 37-39 min (35% A-80% A). Scanning range: 50-1500 m / z, electrospray mode: electrospray positive ion, electrospray voltage 5500 v.

[0059] like Figure 1 As shown, sequencing confirmed that the amino acid sequence of TAP is a hexapeptide of DGFDGL (SEQ ID NO: 1) with a molecular weight of 622.20 Da. This peptide contains 6 amino acids and contains an aromatic amino acid (phenylalanine).

[0060] IC of XOD inhibitory activity of hexapeptide DL6 50 To measure, such as Figure 2 As shown, the XOD inhibitory activity IC of hexapeptide DL6 50 The XOD inhibitory activity of the obtained peptide was significantly higher than that of the peptide ADIYTE (19.01±0.23 mg / mL) derived from defatted and dephenolized walnut powder and the peptide ACECD (7.23 mg / mL) derived from bonito.

[0061] Example 2: Preparation of nanoliposomes encapsulating tuna uricosuric acid-lowering peptide

[0062] A polypeptide with an amino acid sequence of DGFDGL (SEQ ID NO: 1) was synthesized and dissolved in distilled water at a concentration of 5 mg / mL.

[0063] Soy lecithin and cholesterol are dissolved in anhydrous ethanol to obtain a mixed solution; the concentration of soybean lecithin in the mixed solution is 40 mg / mL, and cholesterol is added according to a certain ratio. The mixed solution is treated by magnetic stirring to fully dissolve the solutes in it.

[0064] The polypeptide solution and the mixed solution containing soybean lecithin and cholesterol are mixed evenly according to a certain volume ratio, ultrasonically treated, and then subjected to dynamic high-pressure microfluidization homogenization to obtain nanoliposomes encapsulating uricosuric peptides with a particle size of less than 120 nm and a potential of less than -20 mV.

[0065] Effect of the mass ratio of soybean lecithin to cholesterol (cholesterol-to-lipid ratio) on the encapsulation efficiency, Zeta potential and particle size of nanoliposomes Figure 3 As shown. When the mass ratio of soybean lecithin and cholesterol increased from 1:14 to 1:6, the encapsulation rate first increased and then decreased rapidly. Among them, the encapsulation rate was the highest when the mass ratio of soybean lecithin and cholesterol was 1:12, which was 67.13±0.53%. This may be due to the fact that a higher content of cholesterol will lead to lower symmetry and ductility of the liposomes, as well as poor fluidity and reduced internal space, resulting in a decrease in the encapsulation rate; similarly, too low a cholesterol content will make it difficult for the liposomes to form a film and form a complete liposome vesicle structure, resulting in a low encapsulation rate. At the same time, the absolute value of the liposome Zeta potential shows a trend of first decreasing and then increasing with the increase of the cholesterol-to-fat ratio, and the absolute value of the Zeta potential is the largest when the cholesterol-to-fat ratio is 1:14. The particle size of the liposome shows a trend of first increasing and then decreasing with the increase of the cholesterol-to-fat ratio, and the particle size is the smallest when the cholesterol-to-fat ratio is 1:8. Taking encapsulation efficiency as the main screening index, the cholesterol-lipid ratio of 1:12 was selected as the most suitable preparation condition. Its Zeta potential and particle size were -33.57±1.91mV and 136.57±3.99nm, respectively, indicating that the system was relatively stable and the particle size was small.

[0066] Effect of the volume ratio of peptide to wall material (soy lecithin and cholesterol) solution (core-to-wall ratio) on the encapsulation efficiency, Zeta potential and particle size of nanoliposomes Figure 4 As shown. When the core-to-wall ratio increases from 14:1 to 2:1, the encapsulation rate first increases and then decreases, and the encapsulation rate is the highest when the core-to-wall ratio is 11:1, which is 76.52±0.81%. Too high or too low wall material content will cause uneven peptide embedding, resulting in excess wall material or core material, which will lead to system imbalance and reduced encapsulation rate. At the same time, the absolute value of the liposome Zeta potential shows a trend of first decreasing and then increasing with the change of the core-to-wall ratio, and the absolute value of the Zeta potential is the largest when the core-to-wall ratio is 5:1. The particle size of the liposome shows a trend of first decreasing and then increasing with the increase of the core-to-wall ratio, and the particle size is the smallest when the core-to-wall ratio is 11:1. Taking the encapsulation rate as the main screening index, a core-to-wall ratio of 11:1 was selected as the most suitable preparation condition, and its Zeta potential and particle size were -23.10±1.47mV and 118.50±3.87nm, respectively, indicating that its system is stable and the particle size is small.

[0067] Homogenization pressure is an important parameter in the preparation of liposomes. The effects of different homogenization pressures on the encapsulation efficiency, Zeta potential and particle size of nanoliposomes are shown in Figure 2. Figure 5As shown. When the homogenization pressure is 30-110MPa, the encapsulation rate first increases and then decreases. When the homogenization pressure is 50MPa, the encapsulation rate is the highest, which is 84.47±0.59%. This may be because the 50MPa homogenization pressure is sufficient to handle the liposome system, and further increasing the homogenization pressure will result in poorer results. At the same time, the homogenization pressure has no significant effect on the absolute value of the liposome Zeta potential (p>0.05), while the particle size of the liposome gradually decreases with the increase of the homogenization pressure. Taking the encapsulation rate as the main screening index, a homogenization pressure of 50MPa was selected as the most suitable preparation condition. Its Zeta potential and particle size were -39.70±0.36mV and 132.30±1.06nm, respectively, indicating that its system tends to be stable and the particle size is small.

[0068] Ultrasonic treatment can increase the volume of the dispersed phase and reduce the droplet size, thereby assisting the liposome to embed the uricosuric acid-lowering peptide. The effects of different ultrasonic times on the encapsulation efficiency, Zeta potential and particle size of nanoliposomes are shown in Figure 2. Figure 6 As shown. When the ultrasonic time is 0-80min, the encapsulation rate first increases and then decreases. Among them, the encapsulation rate is the highest when the homogenization pressure is 40min, which is 85.87±0.63%, which is consistent with the trend of previous research results. This is because too short ultrasonic time will cause the liposomes to be unable to fully disperse, so the liposome encapsulation rate is low. Too long ultrasonic time will destroy the stable liposomes, resulting in a decrease in the encapsulation rate, and too long ultrasonic time is likely to damage the physiological activity of active peptides. At the same time, with the increase of ultrasonic treatment time, the absolute value of the liposome Zeta potential first increases and then decreases, while the particle size of the liposome gradually decreases with ultrasonic treatment. Taking the encapsulation rate as the main screening index, the ultrasonic time of 40min was selected as the more suitable preparation condition. Its Zeta potential and particle size were -27.53±1.16mV and 108.27±2.51nm, respectively, indicating that its system tends to be stable and the particle size is small.

[0069] Example 3: Physicochemical properties of nanoliposomes encapsulating tuna uricosuric acid-lowering peptide

[0070] The Zeta potential and particle size of the TAP-NLs prepared in Example 1 were -27.53±1.16 mV and 108.27±2.51 nm, respectively, indicating that the system was stable and the particle size was small. Figure 7 As shown in the figure, the microstructure of the TAP-NLs suspension was observed by TEM. The TEM image showed that the TAP-NLs were spherical, with uniform particle size and clear appearance, and no obvious aggregation in the solvent. In addition, the TEM image showed that the particle size of TAP-NLs was about 100 nm. Similarly, the nanoliposomes loaded with cod meat osteogenic peptide also had a spherical structure, nanoscale size and smooth surface.

[0071] The effect of nanoliposome encapsulation on the chemical structure of uric acid-lowering peptide was studied by Fourier transform infrared spectroscopy (FTIR). Figure 8 ). FTIR is a non-destructive and precise technique used to evaluate the chemical composition, structural arrangement, and functional groups of various compounds. The amide A band of TAP-NLs is located at 3280cm-1, which is slightly blue-shifted compared to TAP. The amide B band of TAP-NLs is located at 2926cm-1, which is also blue-shifted compared to TAP, and the intensity of TAP-NLs is significantly higher than that of TAP, which may be related to the symmetric and asymmetric stretching vibrations of the aliphatic -CH2. In addition, the peak changes between TAP-NLs and TAP at 1653cm-1 and 1642cm-1 are attributed to the -O– vibrations of the heterocycle. In general, the main peaks of TAP-NLs include 3280 cm-1 (NH stretching), 2926 cm-1 (OH stretching), 1653 cm-1 (amide I region and C═O stretching), 1592 cm-1 (amide-II region, such as CN stretching and NH deformation), 1075 cm-1 (C═O stretching) and 672 cm-1 (NH bending). Liposome encapsulation changed the FTIR spectrum of the peptides. After encapsulation of the peptides, the most important changes observed in the nanoliposomes were changes in the amide B band (asymmetric stretching vibration) and the amide III band (CH stretching vibration and NH bending vibration), which are presumably caused by the formation of hydrogen bonds, the entry of hydrophobic peptides into the bilayer membrane, and the formation of ionic complexes between them and phosphatidylcholine groups.

[0072] The crystalline state of uricosuric peptide in liposomes was evaluated by X-ray diffraction (XRD) analysis. In general, crystalline materials exhibit a unique pattern of narrow and well-defined peaks, while amorphous materials produce broad and fuzzy peaks. Fig. 9 As shown, TAP and TAP-NLs exhibit broad and fuzzy peaks, and only a broad characteristic peak is observed at a diffraction angle 2θ of around 20°, indicating that the amorphous structure is dominant in TAP and TAP-NLs, which is similar to the existing results, indicating that TAP is effectively embedded in TAP-NLs and does not have any obvious effect on the characteristic structure of the liposomes.

[0073] The changes of XOD inhibitory activity of prepared liposome TAP-NLs after simulated gastrointestinal digestion in vitro were studied. Fig.10As shown, as the in vitro digestion proceeds, the XOD inhibitory activity of TAP-NLs first decreases and then increases, but there is no significant difference (p>0.05). This may be because soybean lecithin encapsulates the active peptides, preventing them from being digested by enzymes. As the digestion proceeds, the uric acid-lowering peptides are gradually released and absorbed by the intestine to exert their biological activity. The above results show that the liposome encapsulation system constructed by the present invention can effectively prevent the active substances from being destroyed, does not affect the uric acid-lowering activity of the polypeptide, and provides a reference for the encapsulation and transportation of other biologically active substances.

[0074] Since the thermodynamic properties of nanoliposomes are unstable and may lead to leakage of captured compounds, the stability of liposomes is crucial. This paper studies the changes in particle size and Zeta potential of TAP-NLs at different temperatures (-18℃, 4℃ and 25℃). Fig.11 As shown in Figure 2, when stored at -18 °C for 3 days, the particle size of TAP-NLs increased significantly from 115.20 ± 0.95 nm to 451.20 ± 6.17 nm (p < 0.05), and slowly increased to 586.03 ± 13.78 nm (p < 0.05) within 3-28 days, which is similar to the results of existing literature. This may be due to the penetration of ice crystals into the liposome membrane during freezing, the increase in particle size, the compression of liposomes induced by mechanical stress, and the subsequent adhesion and aggregation of TAP-NLs, which ultimately led to the instability of the system. Storage at 4 °C for 28 days had no significant effect on the particle size of TAP-NLs (P> 0.05), which may be attributed to the low permeability and flexibility of the membrane at low temperatures, which makes the molecular mobility of phospholipids lower. Marín et al. also reported that there was no significant difference in the particle size of liposomes containing collagen hydrolysate after storage at 4 °C for 14 days. In addition, after storage at 25°C for 28 days, the particle size of TAP-NLs increased significantly from 115.20±0.95nm to 143.20±3.64nm (p<0.05), but its particle size was still small and in the nanometer range. In general, TAP-NLs had good storage stability at 4°C, and the particle size did not change significantly during the storage period.

[0075] like Fig.11As shown in the figure, within 28 days of storage at -18°C, the Zeta potential of TAP-NLs first increased and then decreased, with a more obvious change. It can be inferred that during the freeze-thaw process, ice crystals can not only generate mechanical stress, but also penetrate into the liposome membrane and lead to the formation of large flocs, which ultimately leads to the instability of the system. Similar to the particle size results, storage at 4°C for 28 days had no significant effect on the Zeta potential of TAP-NLs (p>0.05), which remained at around 26mV. This can be attributed to the decrease in membrane fluidity at lower temperatures, the maintenance of Zeta potential, the prevention of vesicle aggregation and fusion, and the delay of unsaturated fatty acid oxidation, thereby achieving strong electrostatic stability of the dispersion. Studies have also shown that the Zeta potential of all marine phospholipid vesicles did not change significantly during the storage period, and the repulsive force between vesicles led to the stability of nanoliposomes. In addition, after storage at 25°C for 28 days, the Zeta potential of TAP-NLs showed irregular changes.

[0076] In summary, TAP-NLs have good storage stability at 4°C, which can be explained by the fact that low temperature inhibits the disintegration of liposomes. Another possibility for the higher stability of nanoliposomes is that the uric acid-lowering peptide and the phospholipid bilayer interact at the molecular level. In addition, the bilayer has an inhibitory effect on liposome disintegration and acts as a barrier on the liposome surface.

Claims

1. A polypeptide having uric acid-lowering activity, characterized in that: The amino acid sequence of the polypeptide is SEQ ID NO:

1.

2. Use of the polypeptide according to claim 1 in the preparation of a product for lowering uric acid, wherein the product is a nanoliposome.

3. A nanoliposome, characterized in that: The nanoliposome comprises a core material and a wall material, wherein the core material comprises the polypeptide according to claim 1, and the wall material comprises soybean lecithin and cholesterol.

4. The nanoliposome according to claim 3, characterized in that The mass ratio of the soybean lecithin to cholesterol is 1:6-14.

5. The nanoliposome according to claim 4, characterized in that The mass ratio of the soybean lecithin to cholesterol is 1:

12.

6. The nanoliposome according to claim 3, characterized in that The nanoliposomes are prepared by uniformly mixing a core material solution and a wall material solution, ultrasonically treating them, and then subjecting them to dynamic high-pressure microfluidization homogenization treatment to obtain nanoliposomes with a particle size of less than 120nm and a potential of less than -20mV that encapsulate the uricosuric peptide.

7. The nanoliposome according to claim 6, characterized in that The volume ratio of the core material solution to the wall material solution is 2-14:

1.

8. The nanoliposome according to claim 7, characterized in that The volume ratio of the core material solution to the wall material solution is 11:1.

Citation Information

Patent Citations

  • Peanut oligopeptide-coated nano liposome as well as preparation method and application thereof

    CN105902996A

  • Methods for preparing nanoliposome encapsulating proteins and protein-encapsulated nanoliposome

    WO2006109936A1